A social-event based approach to sentiment analysis of identities and behaviors in text. Issue 3 (2nd July 2016) - Joseph, Kenneth; Wei, Wei; Benigni, Matthew; Carley, Kathleen M.
ABSTRACT: We describe a new methodology to infer sentiments held toward identities and behaviors from social events that we extract from a large corpus of newspaper text. Our approach draws on affect control theory, a mathematical model of how sentiment is encoded in social events and culturally shared views toward identities and behaviors. While most sentiment analysis approaches evaluate concepts on a single, evaluative dimension, our work extracts a three-dimensional sentiment "profile" for each concept. We can also infer when multiple sentiment profiles for a concept are likely to exist. We provide a case study of a large newspaper corpus on the Arab Spring, which helps to validate our approach.